Vulvar squamous cell carcinoma arising on human papillomavirus‐independent precursors mimicking high‐grade squamous intra‐epithelial lesion: a distinct and highly recurrent subtype of vulvar cancer. Issue 5 (15th January 2023) - Carreras‐Dieguez, Núria; Saco, Adela; del Pino, Marta; Pumarola, Clàudia; del Campo, Ricardo López; Manzotti, Carolina; Garcia, Adriana; Marimon, Lorena; Diaz‐Mercedes, Sherley; Fuste, Pere; Rodrigo‐Calvo, Maria Teresa; Vega, Naiara; et al.
Abstract : Aims: Each category of vulvar squamous cell carcinoma (VSCC), human papillomavirus (HPV)‐associated and HPV‐independent, arises on a specific intra‐epithelial precursor: high‐grade squamous intra‐epithelial lesions (HSIL) and differentiated vulvar intra‐epithelial neoplasia (dVIN), respectively. However, a subset of HPV‐independent VSCC arises on an intra‐epithelial precursor closely mimicking HSIL. We aimed to explore the clinicopathological features of the HPV‐independent tumours with HSIL‐like lesions and compare them with HPV‐independent VSCC with dVIN and HPV‐associated tumours with HSIL. Methods and results: We retrospectively identified 105 cases of surgically treated VSCC with adjacent intra‐epithelial precursors. The cases were classified into three groups based on the HPV status and the adjacent precursor identified: (i) HPV‐associated VSCC with HSIL ( n = 26), (ii) HPV‐independent VSCC with dVIN lesions ( n = 54) and (iii) HPV‐independent VSCC with HSIL‐like lesions ( n = 25). We analysed the histological and clinical features including the recurrence‐free survival and disease‐specific survival in the three groups. Patients with HPV‐independent VSCC with HSIL‐like lesions and with dVIN were older than patients with HPV‐associated VSCC (76 and 77 versus 66 years, respectively, P < 0.001). HPV‐independent VSCC with HSIL‐like lesions recurred more frequently [hazard ratio (HR) = 3.87; P < 0.001] than HPV‐independent VSCC with dVIN (HR = 2.27; P = 0.1) and HPV‐associated VSCC (HR = 1). In the multivariate analysis, HPV‐independent VSCC with HSIL‐like lesions remained significant for recurrence. No differences in disease‐specific survival were observed between the three groups. Conclusions: Even though VSCC with HSIL‐like lesions are not associated with higher mortality, they are more likely to recur and might benefit from more intensive treatment strategies and closer surveillance after treatment. Abstract : HPV‐independent vulvar carcinomas arising on HSIL‐like lesions show histology identical to HPV‐associated tumours but their immunohistochemical features as well as the absence of HPV and patient's age are similar to HPV‐independent carcinomas. HPV‐independent vulvar cancer arising on HSIL‐like lesions show the highest rates of disease recurrence in comparison with two other groups.